Observation of charge transfer cascades in α-Fe2O3/IrOx photoanodes by operando X-ray absorption spectroscopy. Issue 8 (13th February 2017) - Minguzzi, Alessandro; Naldoni, Alberto; Lugaresi, Ottavio; Achilli, Elisabetta; D'Acapito, Francesco; Malara, Francesco; Locatelli, Cristina; Vertova, Alberto; Rondinini, Sandra; Ghigna, Paolo
Abstract : Electron and hole transfers from an α-Fe2 O3 and an IrO x overlayer are directly observed by means of operando X-ray absorption spectroscopy. Abstract : Electrochemical devices for energy conversion and storage are central for a sustainable economy. The performance of electrodes is driven by charge transfer across different layer materials and an understanding of the mechanistics is pivotal to gain improved efficiency. Here, we directly observe the transfer of photogenerated charge carriers in a photoanode made of hematite (α-Fe2 O3 ) and a hydrous iridium oxide (IrO x ) overlayer, which plays a key role in photoelectrochemical water oxidation. Through the use of operando X-ray absorption spectroscopy (XAS), we probe the change in occupancy of the Ir 5d levels during optical band gap excitation of α-Fe2 O3 . At potentials where no photocurrent is observed, electrons flow from the α-Fe2 O3 photoanode to the IrO x overlayer. In contrast, when the composite electrode produces a sustained photocurrent ( i.e., 1.4 V vs. RHE), a significant transfer of holes from the illuminated α-Fe2 O3 to the IrO x layer is clearly demonstrated. The analysis of the operando XAS spectra further suggests that oxygen evolution actually occurs both at the α-Fe2 O3 /electrolyte and α-Fe2 O3 /IrO x interfaces. These findings represent an important outcome for a better understanding of composite photoelectrodes and their use in photoelectrochemical systems, such as hydrogen generation or CO2 reduction from sunlight.